2009
DOI: 10.1007/s00268-008-9915-z
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults and Riding Position: Factors that Affect Mortality Among Inpatient Adult Motorcycle Casualties: A Major Trauma Center Experience

Abstract: Young motorcycle casualties have a significantly higher mortality rate than older motorcycle casualties. Young passengers have the highest mortality rate and contribute significantly to the death rate among young motorcycle casualties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
(11 reference statements)
0
8
0
1
Order By: Relevance
“…Several governmental reports and scientific studies also suggested that advancing age might be associated with higher risks of suffering severe extensive injury and mortality. 4,8,[15][16][17] Our findings concerning injury pattern and injury severity may hold important implications for the treatment of MTV crash victims and for the prevention of severe injury and mortality after crashes. The results of this study showed that motorized two-wheeled accidents are often associated with injuries in multiple anatomic areas.…”
Section: Discussionmentioning
confidence: 98%
“…Several governmental reports and scientific studies also suggested that advancing age might be associated with higher risks of suffering severe extensive injury and mortality. 4,8,[15][16][17] Our findings concerning injury pattern and injury severity may hold important implications for the treatment of MTV crash victims and for the prevention of severe injury and mortality after crashes. The results of this study showed that motorized two-wheeled accidents are often associated with injuries in multiple anatomic areas.…”
Section: Discussionmentioning
confidence: 98%
“…In Singapore, motorcycle crashes are responsible for 54% of all deaths caused by any motor vehicle accidents [2]. In Italy in 1997 [3], 20% of all deaths due to traffic accidents involved motorcycles while in the United States the number of deaths due to motorcycle crash increased 103% between 1997 and 2006 [4], numbering 2,300 deaths in 1994 and 4,000 in 2004 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the motorcycle usage is more among young male population. [6,[11][12][13][14] Thus, accidents affect the most active section of the society, and result in significant public health problem. Numerous papers were published regarding the nervous system injuries in motor vehicle accidents, yet a very small fraction of them was dedicated to motorcycle accidents.…”
Section: Discussionmentioning
confidence: 99%